Impact of Work Stress on Teacher's Performance: Exploring the impact of work stress on teacher's performance in primary education (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study investigates the complex relationship between stress and job performance amongprimary school teachers and presents its findings. Because a child's academic and personal growth areboth laid to rest during their time in primary education, the function of primary school teachers is of theutmost importance. Nonetheless, the rigors of this profession can cause teachers to experiencesubstantial stress, which can invariably have an effect on how well they accomplish their workresponsibilities. This research investigates the complex nature of stress, its sources, and theconsequences that it has on the job performance of primary school teachers through a thoroughanalysis of the available literature on the topic. We also investigate the many coping techniques andinterventions that are available to reduce the effects of stress and improve the overall performance ofteachers. The findings highlight how important it is to reduce stress among primary school teachers inorder to ensure that quality education is provided to students.